Comprensión lectora de texto en estudiantes de décimo año de educación general básica del colegio nacional Técnico Pasaje 2013-2014. - Capón Sizalima, Ana Isabel (2014)
The level of reading comprehension of the students is low, for that reason the application of the proposal was made that consisted of a seminar workshop on reading comprehension techniques, addressed to the teachers of the tenth year of the different assignactures,